Rethinking the legal nature of an obligation to remedy damage - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In this paper the autors analyse the legal nature of an obligation to remedy damage following the changes introduced by the so-called February amendment. The authors prove, in numerous ways, that despite lawmakers’ declarations, the legal nature of this measure has not changed significantly. Its compensatory abilities were enhanced; nevertheless, the change of the name tag is insufficient to assume that the obligation to remedy damage has become a pure civil act in criminal proceedings. The essence and structure of an obligation to remedy damage are still criminal-law, although its content, by the operation of criminal law, is highly influenced by civil law. As a result, in the case of this measure we are dealing with a criminal-law obligation to remedy damage shaped in accordance with the provisions of civil law.
Keywords: obowiązek naprawienia szkody; odszkodowanie; prawo karne